HUBUNGAN ANTARA PROSES PEMBELAJARAN DI MAJELIS TA’LIM AR-RIDHO DENGAN TINGKAT PEMAHAMAN AJARAN ISLAM PADA MASYARAKAT DESA CIPAYUNG DATAR RT/RW 02/03 KECAMATAN MEGAMENDUNG KABUPATEN BOGOR - Khoerun, Muhamad (Inspiratif Pendidikan, 2021)
This study aims to determine the relationship between the learning process in the majelis ta’lim Ar-ridho with the level of understanding of Islamic teachings in the community of Cipayung Datar Village Rt / Rw 02/03, Megamendung District, Bogor Regency. This study uses a quantitative method with a correlational approach. Sampling in this study using census techniques. Making the entire population as a sample is 50 respondents. Data collection methods namely questionnaires, data processing techniques and data analysis used validity test, normality test, reliability test. While the hypothesis testing uses the Pearson correlation statistics. The results of the normality test are in the normal category between the learning process in majelis ta’lim with the level of understanding of Islamic teachings with a sig> 0.05. Then the results of hypothesis testing between the learning process in majelis ta’lim with the level of understanding of Islamic teachings in the community there is a moderate correlation with the Pearson correlation value of 0.579, which is significant (sig <0.05).